Criminological Review of Domestic Violence Crimes in Kolaka Regency - Irabiah, Irabiah; Jusafri, Jusafri; Al Fitra, Muh. Risaldy (Faculty of Law, Universitas Sembilanbelas November Kolaka, 2024)
This thesis aims to find out what factors cause perpetrators to commit criminal acts of domestic violence in the jurisdiction of theKolaka District resort police, and also to find out the efforts made by the Kolaka District resort police in dealing with criminal acts of domestic violence. This research uses research methods Empirical law, namely this research is carried out directly on legal phenomena in society or social facts found in society. Based on the results of the research and discussion, it can be concluded that what are the factors that cause perpetrators to commit criminal acts of domestic violence in the jurisdiction of the Kolaka District Resort Police, namely economic factors, infidelity factors, alcoholic beverage factors and then to find out the efforts made by the Kolaka District Resort Police Kolaka in dealing with criminal acts of domestic violence, namely conducting outreach or seminars, namely collaborating with regional government institutions, sub-district offices, social services, and sub-district offices and others.